(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The main objective of the current investigation was to develop and evaluate the drug-in-adhesive patches of metoprolol succinate. Materials and Methods: Transdermal patches were formulated using various pressure sensitive adhesives such as Duro-Tak 387-2051, Duro-Tak 387-2052, Duro-Tak 87-2677, Duro-Tak 387-2051, and Duro-Tak 387-2052 alone and/or in combination. The patches were evaluated for different physical parameters with in vitro permeation and ex vivo permeation studies. Skin irritation studies are conducted using albino rats. Results and Discussion: Transdermal patch prepared with drug from formulation F1 was very controlled. F1 has selected for the further studies. Optimization was, therefore, effected by casting the patch at various drug concentrations, viz., 1%, 2%, 3% and 4% w/v and using permeation enhancer (l-menthol). The permeation of the drug from formulation F1 was very controlled, and gradual enhancement of the drug permeation through the skin was noticed in comparison to other formulations. The formulation F7 was made up of Duro-Tak 87-2677, although, released the drug very slowly but due to poor tackiness, this formulation was not further explored. Conclusion: The result obtained showed Duro-Tak formulations, with the exception of Duro-Tak 87- 2677, were able to deliver the drug for extended period of time without causing any skin toxicity. Overall, Duro-Tak formulations showed sufficient promise in the development of an efficient transdermal drug delivery system for the controlled drug delivery of Metoprolol Succinate.